The Lotus japonicus ROP3 Is Involved in the Establishment of the Nitrogen-Fixing Symbiosis but Not of the Arbuscular Mycorrhizal Symbiosis - García-Soto, Ivette; Boussageon, Raphael; Cruz-Farfán, Yareni Marlene; Castro-Chilpa, Jesus Daniel; Hernández-Cerezo, Liz Xochiquetzal; Bustos-Zagal, Victor; Leija-Salas, Alfonso; Hernández, Georgina; Torres, Martha; Formey, Damien; Courty, Pierre-Emmanuel; Wipf, Daniel; et al. (Frontiers in Plant Science, 2021)
Legumes form root mutualistic symbioses with some soil microbes promoting their growth, rhizobia, and arbuscular mycorrhizal fungi (AMF). A conserved set of plant proteins rules the transduction of symbiotic signals from rhizobia and AMF in a so-called common symbiotic signaling pathway (CSSP). Despite considerable efforts and advances over the past 20 years, there are still key elements to be discovered about the establishment of these root symbioses. Rhizobia and AMF root colonization are possible after a deep cell reorganization. In the interaction between the model legume Lotus japonicus and Mesorhizobium loti, this reorganization has been shown to be dependent on a SCAR/Wave-like signaling module, including Rho-GTPase (ROP in plants). Here, we studied the potential role of ROP3 in the nitrogen-fixing symbiosis (NFS) as well as in the arbuscular mycorrhizal symbiosis (AMS). We performed a detailed phenotypic study on the effects of the loss of a single ROP on the establishment of both root symbioses. Moreover, we evaluated the expression of key genes related to CSSP and to the rhizobial-specific pathway. Under our experimental conditions, rop3 mutant showed less nodule formation at 7- and 21-days post inoculation as well as less microcolonies and a higher frequency of epidermal infection threads. However, AMF root colonization was not affected. These results suggest a role of ROP3 as a positive regulator of infection thread formation and nodulation in L. japonicus. In addition, CSSP gene expression was neither affected in NFS nor in AMS condition in rop3 mutant. whereas the expression level of some genes belonging to the rhizobial-specific pathway, like RACK1, decreased in the NFS. In conclusion, ROP3 appears to be involved in the NFS, but is neither required for intra-radical growth of AMF nor arbuscule formation.